HnRNP Q Has a Suppressive Role in the Translation of Mouse Cryptochrome1. - Ilgye Lim; Youngseob Jung; Do-Yeon Kim; Kyong-Tai Kim (PLoS ONE, 2016)
Precise regulation of gene expression is especially important for circadian timekeeping which is maintained by the proper oscillation of the mRNA and protein of clock genes and clock-controlled genes. As a main component of the core negative arm feedback loops in the circadian clock, the Cry1 gene contributes to the maintenance of behavioral and molecular rhythmicity. Despite the central role of Cry1, the molecular mechanisms regulating expression levels of Cry1 mRNA and protein are not well defined. In particular, the post-transcriptional regulation of Cry1 mRNA fate decisions is unclear. Here, we demonstrate that hnRNP Q binds to mCry1 mRNA via the 5'UTR. Furthermore, hnRNP Q inhibits the translation of mCry1 mRNA, leading to altered rhythmicity in the mCRY1 protein profile.